2020
DOI: 10.1038/s41598-020-60298-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of link removal strategies in real complex weighted networks

Abstract: In this report we offer the widest comparison of links removal (attack) strategies efficacy in impairing the robustness of six real-world complex weighted networks. We test eleven different link removal strategies by computing their impact on network robustness by means of using three different measures, i.e. the largest connected cluster (LCC), the efficiency (Eff) and the total flow (TF). We find that, in most of cases, the removal strategy based on the binary betweenness centrality of the links is the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 50 publications
2
61
0
Order By: Relevance
“…The binary network approach has the advantages of simplicity and low computational cost and is straight-forward in gathering information to describe the network. Nonetheless, recent analyses showed that a thorough description of real networks should consider the heterogeneity of the links-interactions [34][35][36][37]. In fact, almost all real networks are characterized by links with different "weights" indicating the strength of the interaction among nodes.…”
Section: Binary and Weighted Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…The binary network approach has the advantages of simplicity and low computational cost and is straight-forward in gathering information to describe the network. Nonetheless, recent analyses showed that a thorough description of real networks should consider the heterogeneity of the links-interactions [34][35][36][37]. In fact, almost all real networks are characterized by links with different "weights" indicating the strength of the interaction among nodes.…”
Section: Binary and Weighted Networkmentioning
confidence: 99%
“…Even in this case, the LCC is not able to evaluate the network functioning decrease, probably underestimating its damage. For these reasons, even when adopted in weighted networks, the LCC returns a pure topological description, neglecting to evaluate the underlying weighted structure [34][35][36][37].…”
Section: The Network Functioning Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently, the weighted shortest paths (wSP) consider both the number of links and the weight attached to them. To compute wSP, we first compute the inverse of the link weights; then we compute the weighted shortest paths as the minimum sum of the inverse link weights necessary to travel among nodes [27,34] .…”
Section: The Network Efficiency (Eff)mentioning
confidence: 99%
“…We find that the removal towards the core Chls is clearly more harmful in decreasing the PSI functioning, suggesting the core as the key structural component of the high efficiency EET in the PSI of the P. Sativum.where the element wi,j>0 in the case there is link of weight wi,j between the node i and the node j and wi,j=0 otherwise. Many empirical researches demonstrate that purely binary-topological models are inadequate to explain the complex structure of the real systems, and that there is a need for weighted network models to overcome the pure topological description [27,28,34]…”
mentioning
confidence: 99%